2014
DOI: 10.1186/1865-1380-7-8
|View full text |Cite
|
Sign up to set email alerts
|

The probability of patients being admitted from the emergency department is negatively correlated to in-hospital bed occupancy – a registry study

Abstract: BackgroundThe association between emergency department (ED) overcrowding and poor patient outcomes is well described, with recent work suggesting that the phenomenon causes delays in time-sensitive interventions, such as resuscitation. Even though most researchers agree on the fact that admitted patients boarding in the ED is a major contributing factor to ED overcrowding, little work explicitly addresses whether in-hospital occupancy is associated to the probability of patients being admitted from the ED. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Considering our previous results, which showed that the probability for being admitted from the ED is lower at times of high in-hospital occupancy [[17]], the present results suggest that ED physicians make good decisions, also when resources are constrained.…”
Section: Discussionsupporting
confidence: 62%
“…Considering our previous results, which showed that the probability for being admitted from the ED is lower at times of high in-hospital occupancy [[17]], the present results suggest that ED physicians make good decisions, also when resources are constrained.…”
Section: Discussionsupporting
confidence: 62%
“…Although evidence is conflicting, 32 hospital crowding has been shown to result in a reduced chance of admission. 33 Furthermore, it is well established in the literature that hospital crowding is a major limiting factor of ED throughput, leading to increasing inpatient boarding. 20,[34][35][36] Therefore, while we did not have access to hospital crowding data, we provided an estimate of hospital crowding by examining the boarding times of patients entering the ED.…”
Section: Discussionmentioning
confidence: 99%
“…The number of boarding patients gradually increases from Monday to Friday, and then decreases on Friday afternoon. The median (IQR) value was 56 (44-68) for the total number of patients, 35 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) for the number of evaluating patients, and 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) for the number of boarding patients. Therefore, the third quartile, the critical point of overcrowding was 68, 44, and 26, for total, evaluating, and boarding indicators, respectively.…”
Section: Resultsmentioning
confidence: 99%